Clinical significances and prognostic value of cancer stem‐like cells markers and vasculogenic mimicry in renal cell carcinoma. Issue 6 (29th August 2013) - Zhang, Yanhui; Sun, Baocun; Zhao, Xiulan; Liu, Zhiyong; Wang, Xudong; Yao, Xin; Dong, Xueyi; Chi, Jiadong
Abstract Background The aim of this study was to investigate the clinical significances and prognostic value of CD133 and CD44 (markers of cancer stem‐like cells, CSCs), and vasculogenic mimicry (VM) in renal cell carcinoma (RCC). Methods Immunohistochemistry was performed to detect CD133 and CD44 expression and VM in 110 RCC patients proven to exhibit de novo metastases after radical nephrectomy. Results In RCC, positive rates of 27.3%, 20.9%, and 21.8% were obtained for CD44, CD133, and VM, respectively. CD44 was significantly associated with tumor size, grade, stage, and histological type. CD44 expression may serve as a predictor of the number of metastases sites in RCC. CD133 expression correlated with tumor grade, stage, histological type, and tumor location. VM was positively associated with tumor grade and stage. Microvessel density (MVD) positively corresponded to tumor size, grade, and stage. CD133 expression was not associated with MVD, but significantly correlated with VM. CD44 expression correlated marginally with VM, but was found to have a significantly association with MVD. A close relationship between CSCs, MVD, and VM was established. The overall survival times of patients with CD133‐high positive, CD44‐high positive, VM‐positive, and MVD <43 were lower than that of the patients with low positive, negative, and MVD ≥43. Tumor grade and presence of VM were independent prognostic factors of RCC. Conclusions Findings show that higher CSCs and VM was correlated with more aggressive clinicopathologic. VM was an independent unfavorable prognostic factor. The authors consistently observed that CSCs may be related to angiogenesis and vasculogenic mimicry. J. Surg. Oncol. 2013; 108:414–419. © 2013 Wiley Periodicals, Inc.